COVID-19 Effects on Livestock Production: A One Welfare Issue - Marchant-Forde, Jeremy N.; Boyle, Laura A. (Frontiers in Veterinary Science, 2020)
The COVID-19 pandemic highlights that we exist in a global community. From a single city, it spread to 188 countries across the world and infected 25 million people by August 30, 2020. Decades of modelling pandemics predicted potential consequences, but COVID-19’s impact on the food supply chain, and specifically livestock production was unexpected. Clusters of cases among workers in meat processing plants evolved quickly to affect human, animal and environmental welfare in several countries. In processing plants, the hygiene focus is on product quality and food safety. Because of their close proximity to one another, COVID-19 spread rapidly between workers and the lack of sick leave and health insurance likely resulted in workers continuing to work when infectious. In the United States (U.S.) many processing plants shut down when they identified major outbreaks, putting pressure especially on pig and poultry industries. At one point, there was a 45% reduction in pig processing capacity meaning about 250,000 pigs per day were not slaughtered. This resulted in longer transport distances to plants in operation with extra capacity, but also to crowding of animals on farm. Producers were encouraged to slow growth rates, but some had to cull animals on farm in ways that likely included suffering and caused considerable upset to owners and workers. Carcass disposal was also associated with potential biosecurity risks and detrimental effects on the environment. Hence, this is a One Welfare issue, affecting human, animal and environmental welfare and highlighting the fragility of intensive, high-throughput livestock production systems. This model needs to be re-shaped to include the animal, human and environmental elements across the farm to fork chain. Such a One Welfare approach will ensure that food production systems are resilient, flexible and fair in the face of future challenges.